Analysis of Differentiated Approach Effectiveness in Patients with Varying Degrees of Severity of Chronic Ocular Ischemic Syndrome Caused by Internal Carotid Artery Stenosis - V. V. Tuzlaev; V. V. Egorov; I. Z. Kravchenko; G. P. Smoliakova (Oftalʹmologiâ)
Purpose: to study the effect of differentiated treatment approach in patients with varying degrees of severity chronic ocular ischemic syndrome (OIS) on clinical course of disease and hemodynamics of eyes in prospective research.Patients and methods. The research included 20 patients with chronic OIS. Patients were divided into 4 groups due to severity of chronic OIS and type of treatment. 1st group — 7 patients with moderate severity chronic OIS and hemodynamically significant of internal carotid artery stenosis (ICAS); only carotid endarterectomy (CE) of ICAS was performed. 2nd group — 6 patients with severe degree chronic OIS and hemodynamically significant stenosis of ICAS; 2 weeks before CE, panretinal photocoagulation (PRP) of retinal capillary non-perfusion areas was performed. 3rd group — 4 patients with severe degree chronic OIS, complicated by rubeosis iris and increased IOP on hypotensive regimen, on the background of hemodynamically insignificant ICAS; PRP of retina was performed. 4th group — 3 patients with moderate severity chronic OIS with hemodynamically insignificant ICAS; course of neuroprotective therapy was performed. All patients underwent standard and specialized ophthalmologic examination methods. Assessment of blood flow in brachiocephalic vessels, eye vessels was performed by ultrasound scan, spiral computed tomography, OCT-angiography with the AngioVue.Results. Monitoring of patients’ groups for 1 year after chronic OIS treatment allowed us to determine tactics of patient management depending on degree of ICAS and severity of chronic OIS. Reconstructive surgery at hemodynamically significant ICAS caused positive dynamic in intraocular blood flow, which contributed to improvement and preservation of BCVA in 71 % of patients. Preventive PRP of retina, before performing reconstructive surgery of ICAS, optimized and reduced the time of visual recovery. PRP of retina as independent method of treatment of chronic OIS, complicated by neovascular glaucoma, caused full or partial regression of neovascularization in iris, which increased possibilities of its effective treatment. Neuroprotective pharmacotherapy in early stages of chronic OIS, in absence of indications for reconstructive surgery and PRP of retina, improved the prognosis for patients’ vision.Conclusion. Differentiated treatment approach in patients with chronic OIS, due to changes of hemodynamics of internal carotid artery, has improved indexes of hemodynamic and visual acuity.